You should use the sum `pi/3 + pi/4` instead of result `7pi/12` such that:

`tan 7pi/12 = tan (pi/3 + pi/4)`

You need to use the following formula such that:

`tan(a+b) = (tan a + tan b)/(1 - tan a*tan b)`

Reasoning by analogy yields:

`tan (pi/3 + pi/4) = (tan (pi/3)+ tan (pi/4))/(1 - tan (pi/3)*tan (pi/4))`

Using `tan (pi/3) = sqrt3` and `tan (pi/4) = 1` yields:

`tan (pi/3 + pi/4) = (sqrt3 + 1)/(1 - sqrt3)`

`tan (pi/3 + pi/4) = ((sqrt3 + 1)^2)/(1 - 3)`

`tan (pi/3 + pi/4) = (4 + 2sqrt3)/(-2)`

`tan (pi/3 + pi/4) = -2 - sqrt3`

**Hence, evaluating the tangent of angle `7pi/12 ` using the sum `pi/3 + pi/4` yields `tan 7pi/12 =-2 - sqrt3` .**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now